AN INVESTIGATION INTO METAPHORS RELATED TO THE CONCEPT OF “DIGNITY” IN OLIVER TWIST BY CHARLES DICKENS VIA ITS VIETNAMESE VERSION TRANSLATED BY PHAN NGOC - TRƯƠNG THỊ HỒNG MINH (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Literature is considered a valuable treasure of all nations. It will be a missing if we do not mention a great novelist of the in English literature and the creator of some of the world's memorable fictional characters - Charles Dickens since his literary works are well-known in many aspects: plot, setting and experiences. Up to now, his novels still remain captivating to his audience and they seem to be valuable life lessons and experiences for readers. Throughout Oliver Twist, the author reflects vividly what the money does to people, and the impact of goods and evils on individuals’ lives. This study attempts to investigate metaphors denoting the concept of “dignity” in Oliver Twist by Charles Dickens through its Vietnamese translational version by Phan Ngoc. The purpose is to find out strategies the most commonly used by the translator when translating metaphors related to the concept of “dignity”. These strategies are arranged in order of frequency. Then, the phenomena of loss and gain in meaning during the translating process will be also presented. Basing on the findings of the study, some implications for the teaching and learning of language will be suggested.